THE TEENEGERS’ CHARACTERISTICS IN GENDER WRITTEN TEXT BY DISCOURSE ANALYSIS AT BATAM - Frangky Silitonga (Kajian Linguistik dan Sastra, 2017)
This paper gives a clear picture of the differences and competence of teenagers in Batam on producing gender written texts. This article also analyzed short coherent paragraphs by two different gender groups: male and female groups. Discourse analysis was employed to analyze the data – two different pictures. The data of this qualitative research comprise words, clauses and sentences classified into nouns, verbs, adjectives and adverbs. The researcher focused on the characteristics of both genders in expressing their ideas; self- confidence, doubt, language skills and logic. It is found that female students produced more words particularly nouns than those of males.Keywords: Characteristics, written, gender, comprise words, sentences